Is it herpes or aphthae lesions? - Sufiawati, Irna; Pradono, Siti Aliyah (Padjadjaran Journal of Dentistry, 2008)
Recurrent intraoral herpetic (RIH) and recurrent aphthous stomatitis (RAS) are common oral disorders and these diagnosis are often mistaken for one another. The confusion associated with developing an accurate diagnosis is somewhat understandable since these two very different lesions share some common characteristics. Misdiagnosis may result in effective treatment, thereby worsening the lesion. We reported 4 cases to evaluate these similarities and differences, includes the patients history, information regarding initiating factors, frequency of lesions, relieving factors, aggravating factors, the physical examination, and the results of any indicated tests, which are important data to the diagnostic process of these two lesions. By considering these data, an accurate diagnosis of theses two common oral disordes can be developed. It’s concluded that RIH and RAS have some similarities and differences, which are very important to developing an accurate diagnosis and the treatment plan, therefore the dental and oral health professional must be knowledgeable in defferentiating between RIH and RAS.